Agricultural Crops as Potential Source of Bio-fuel Production - Kumar, Sudhir; Manukonda, Srinivas; Satyanarayana, P. V.; Ramanjaneyulu, A. V. (International Journal of Economic Plants, 2015)
Need for bio-fuel production is gaining momentum due to ever increasing environmental pollution and sky rocketing of prices of fossil fuels. These has led to worldwide interest in the production and use of bio-fuels. Policies have been made in both the developed and developing countries to encourage production of combustible fuels from plants that triggered public and private investments in bio-fuel crop research, development and production. This article emphasizes potential benefits of bio-fuel crops and important role played by them in reducing the environmental pollution and in increasing the farmers’ income. This article also gives an insight into various bio-fuel crops being cultivated for production of bio-ethanol or bio-diesel and a brief review of current status of investigations on bio-fuel crops.